Precise intracellular uptake and endosomal release of diverse functional mRNA payloads via glutathione-responsive nanogels - Rupali Dabas; Naveenan Navaratnam; Haruki Iino; Saidbakhrom Saidjalolov; Stefan Matile; David Carling; David S. Rueda; Nazila Kamaly (Materials Today Bio)
We present a novel, highly customizable glutathione-responsive nanogel (NG) platform for efficient mRNA delivery with precise mRNA payload release control. Optimization of various cationic monomers, including newly synthesized cationic polyarginine, polyhistidine, and acrylated guanidine monomers, allowed fine-tuning of NG properties for mRNA binding. By incorporating a poly(ethylene) glycol-based disulphide crosslinker, we achieved glutathione-triggered mRNA release, enabling targeted intracellular delivery. Our NGs demonstrated superior encapsulation (up to 89.3 %) and loading (10.7 %) efficiencies, with controlled mRNA release kinetics at intracellular glutathione concentrations. NGs outperformed commercial transfection reagents across multiple cell lines, including traditionally difficult-to-transfect lines. We demonstrate the platform's versatility by successfully delivering GFP mRNA, Mango II RNA aptamers, and functionally relevant β2-AMPK mRNA. Furthermore, we used TIRF microscopy to measure exact RNA copy number within the NGs. Notably, mechanistic cellular uptake studies revealed that disulphide-containing NGs exhibit enhanced cellular uptake and endosomal escape, potentially due to interactions with cell surface thiols. This work represents a highly tuneable, efficient, and biocompatible platform for mRNA delivery with relevance for gene therapy and vaccine development.